Sanctity as literature in late medieval Britain - Contzen, Eva von; Bernau, Anke (Manchester University Press, 2015)
This title explores how sanctity and questions of literariness are intertwined across a range of medieval genres.
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism.; Religion in literature.; Saints in literature.; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique.; Religion dans la littérature.; Saints dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; English literature -- Middle English; Religion in literature; Saints in literature; 1100-1500; British Isles.; Sanctity.; literariness.; medieval literature.; poetics.; Literary criticism; Criticism, interpretation, etc.; Literary criticism.; Critiques littéraires.